THE EMERGENCE AND EVOLUTION OF ARABESQUE AS A MULTICULTURAL STYLISTIC FUSION IN ISLAMIC ART: THE CASE OF TURKISH ARCHITECTURE - M. Arif Kamal, Murat Cetin (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2011)
This paper elucidates the emergence and evolution of arabesque with specific reference to the case of arabesque in Turkish art and architecture. It is argued here that arabesque is a fusion of styles rather than a pure and homogenous style. Furthermore, the paper aims to show that although the arabesque style appears to be a fanciful and freely organized manner of artistic treatment it is based on a very complex mathematical logic which is expressed through abstractionism. In this context, the grammar of geometry is elaborately used in the implementation of abstraction. Here, general characteristics as well as different modes or types of arabesque are discussed. Starting with the etymological roots of the term, the history of its use in the literature is explored through the paper. After the inquiry of its material and pragmatic aspects, the development of the arabesque style is evaluated with regard to its transformations that took place along with its injection to Anatolia and mixing with Turkish culture. Finally, the morphological character of this fusion is put forward. Keyword: Morphological character, geometry, fusion of styles, arabesque